Comparative study of the performance of photovoltaic and photovoltaic thermal solar systems: Case study in El Jadida - El Alami Yassine; Ouerradi Fatima; Bounouar Said; Benhmida Mohammadi; Rhiat Mohammed; Benhala Bachir; Hirech Kamal; Baghaz Elhadi (E3S Web of Conferences)
The productivity of photovoltaic (PV) and photovoltaic thermal (PVT) systems depends on environmental conditions and can vary considerably depending on the geographical area. In this study, we evaluated and compared the actual performance of a commercial water-based PVT system (PVT Dualsun Spring) with that of a PV system (PV Dualsun Flash) under the specific conditions of the city of El Jadida. The results show that the PVT system offers better performance than the PV system, mainly thanks to the cooling that reduces the temperature of the cells. When irradiance reaches a maximum of 1055.6 W/m2, the PVT system generates 3.92% more electrical power than the PV system. In addition, its electrical efficiency is 4.11% higher than that of the PV system.